Africa : : Education of African communities in economic and social development in native territories - Mumford, William Bryant; Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1937)
Colonial Office file relating to education policy in the British colonies in Africa; includes the copy of an article from the Journal of the Royal African Society, v. 36, no. 142 (Jan. 1937), p. 17-32: Education in British African dependencies : a review of the 1935 annual reports on native education in Nyasaland, N. Rhodesia, Tanganyika, Uganda, Gold Coast, Nigeria and Sierra Leone / W. Bryant Mumford and B.N. Parker